Amaranthus powellii (Amaranthaceae), a new addition for the flora of India and a preliminary list of the Indian Amaranthus species - Arya, Sindhu; Iamonico, Duilio; Anil Kumar, Venugopalan Nair Saradamma (Hacquetia, 2021)
Three populations of Amaranthus powellii were discovered in Kerala region (SE-India), representing the first record of this species for the national flora. A morphological description based on the Indian plants, as well as ecological data are given. A preliminary list of all the Amaranthus species occurring in India, which was never published during the last 135 years, is also provided.